2011
DOI: 10.1071/py10075
|View full text |Cite
|
Sign up to set email alerts
|

Why do we not use trained interpreters for all patients with limited English proficiency? Is there a place for using family members?

Abstract: Australia and New Zealand both have large populations of people with limited English proficiency (LEP). Australia's free telephone interpreter service, which is also used by New Zealand through Language Line (LL) but at a cost to the practices, is underused in both countries. Interpreter guidelines warn against the use of family members, yet the lack of uptake of interpreter services must mean that they are still often used. This paper reviews the literature on medical interpreter use and reports the results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(87 citation statements)
references
References 44 publications
3
83
0
1
Order By: Relevance
“…This is particularly important as the delivery of quality primary care health service to a CALD population needs to incorporate an interpreter resulting in longer consultations [46]. Gray et al [47] has shown that an in-house interpreter was rated as most appropriate during consultations at a primary care health care centre in New Zealand when compared to the use of family members and telephone interpreters.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important as the delivery of quality primary care health service to a CALD population needs to incorporate an interpreter resulting in longer consultations [46]. Gray et al [47] has shown that an in-house interpreter was rated as most appropriate during consultations at a primary care health care centre in New Zealand when compared to the use of family members and telephone interpreters.…”
Section: Discussionmentioning
confidence: 99%
“…Despite recommendations for using interpreter services (13), limitations of interpreter services resulted in nursing personnel relying more heavily on other communication aids. Informants' perceptions suggest that improved interpreter services' availability and accessibility would save time and improve care, especially on weekends when interpreter services' availability is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Problems such as accessing interpreter agencies, interpreters not respecting booked consultations, and poorly functioning technical equipment (14). In other previous studies the authors have shown that healthcare professionals experience a lack of easily available interpreters (15, 16) complications in communicating with using an interpreter (17, 18) not least because of lack of training in the practical use of interpreters and also because of financial considerations (18, 19). …”
Section: Introductionmentioning
confidence: 95%